2013
DOI: 10.3109/03008207.2012.748757
|View full text |Cite
|
Sign up to set email alerts
|

Novel Threadlike Structures on the Surfaces of Mammalian Abdominal Organs are Loose Bundles of Fibrous Stroma with Microchannels Embedded with Fibroblasts and Inflammatory Cells

Abstract: Novel threadlike structures (NTSs) on the surfaces of mammalian abdominal organs have recently attracted interests regarding their ability to transport fluid, enable cell migration, and possibly facilitate cancer metastasis. Nevertheless, histological studies of NTSs have been sporadic and often have inconsistent interpretations of the NTS internal structure. In this article, we provide a synthetic and consistent view of the NTS internal structure: the NTS is a loose bundle of fibrous stroma that forms interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In addition, the presence of 1 ~ 2 mL sized DNA-containing granules in the liquid extracted from the corpuscles is unique to NTSs, whereas lymph vessels carry lymphocytes that are 5  μ m or larger. The alignment of rod-shaped nuclei along the major axis of NTSs is accepted as one of the characteristics that can be used to discriminate NTSs from other similar-looking tissues or artifacts [13]. Our fluorescence images of DAPI-stained structures (Figure 3) showed that the rod shape and linear alignment of the nuclei aligned the major axis of the NTS.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the presence of 1 ~ 2 mL sized DNA-containing granules in the liquid extracted from the corpuscles is unique to NTSs, whereas lymph vessels carry lymphocytes that are 5  μ m or larger. The alignment of rod-shaped nuclei along the major axis of NTSs is accepted as one of the characteristics that can be used to discriminate NTSs from other similar-looking tissues or artifacts [13]. Our fluorescence images of DAPI-stained structures (Figure 3) showed that the rod shape and linear alignment of the nuclei aligned the major axis of the NTS.…”
Section: Discussionmentioning
confidence: 78%